2015
DOI: 10.2119/molmed.2015.00198
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase and Glycogen Synthase Kinase 3β Modulate the Severity of Sepsis-induced Lung injury

Abstract: Alterations in metabolic and bioenergetic homeostasis contribute to sepsis-mediated organ injury. However, how AMP-activated protein kinase (AMPK), a major sensor and regulator of energy expenditure and production, affects development of organ injury and loss of innate capacity during polymicrobial sepsis remains unclear. In the present experiments, we found that cross-talk between the AMPK and GSK3β signaling pathways controls chemotaxis and the ability of neutrophils and macrophages to kill bacteria ex vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 70 publications
(95 reference statements)
7
57
1
Order By: Relevance
“…The activity of 5 -AMP-activated protein kinase (AMPK) may be central to these mechanisms, as it was recently shown that administration of an AMPK activator (metformin) could protect mice in a model of sepsis-induced lung injury. This protection was thought to be mediated by a mechanism that includes decreased neutrophil accumulation, attenuated HIF1 signalling and decreased epithelial permeability in the lung 114 .…”
Section: Hypoxia In Pathological Immune Nichesmentioning
confidence: 99%
“…The activity of 5 -AMP-activated protein kinase (AMPK) may be central to these mechanisms, as it was recently shown that administration of an AMPK activator (metformin) could protect mice in a model of sepsis-induced lung injury. This protection was thought to be mediated by a mechanism that includes decreased neutrophil accumulation, attenuated HIF1 signalling and decreased epithelial permeability in the lung 114 .…”
Section: Hypoxia In Pathological Immune Nichesmentioning
confidence: 99%
“…Alveolar epithelial AMPK can be activated, for example by high CO2 levels[57]. In a bacterial model of ALI, AMPK activation in the lung was shown to be immunosuppressive, hence protective against ALI[59]. Hence, the extent to which the Ca 2+ -CAM → CAMKKβ → AMPK activation cascade promotes lung repair in ALI requires further consideration.…”
Section: The Role Of Cell Ca2+mentioning
confidence: 99%
“…However, recovery of metabolic activity and organ function is possible, and were strongly regulated by expression of markers of mitochondrial biogenesis such as PRARgamma-coactivator-1a (PGC-1a), nuclear respiratory factors 1 and 2 (NRF-1 and -2), and via repression of the biogenesis suppressor nuclear receptor interacting protein-140 (RIP140) [37464748]. Moreover, most recent pre-clinical studies, and our results, indicated that not only preservation, but also mitochondrial biogenesis is an essential step in reestablishing immune or tissue organ homeostasis during recovery from sepsis [495051]. …”
Section: Mitochondrial Dysfunction Correlates With Sepsis-related Mulmentioning
confidence: 86%
“…In particular, dissipation of mitochondrial membrane potential, a situation found upon exposure to bacterial product LPS, nearly completely diminished neutrophils chemotaxis [5070]. This is relevant issue because host-generated inflammatory mediators and bacterial products are present in circulation of individuals with established sepsis.…”
Section: Metabolic Control Of Immune Cell Homeostasis and Pro-inflammmentioning
confidence: 99%